Allowing Tax Rate Adjustment to Increase Local Original Income - Soebroto , Bambang; Puspita , Ayu Fury (RISK : Jurnal Riset Bisnis dan Ekonomi, 2024)
This study aims to analyze the impact of adjusting local tax rates on PAD with the emergence of UU no. 11 of 2020 Article 114 which states that central government can intervene in regional tax policies. This research method is quantitative-descriptive with primary data from BAPENDA Malang City. Data processing uses formula approach to obtain potential projections, targets, realization for this year and following years. The results show that PPJ rates are estimated to increase by 10%, the same as the maximum limit in UU no. 34 of 2000. Furthermore, these results were increased to optimal level, where the potential revenue and local tax target for Malang City in 2022 with moderate economic growth were IDR 835,835,006,350.69 and IDR 831,655,831,318.94, respectively.